Adsorption of copper (II) and nickel (II) by chemical modified magnetic biochar derived from eichhornia crassipes - Chaiyaraksa, Chompoonut; Boonyakiat, Watcharapol; Bukkontod, Wannisa; Ngakom, Wanvisa (My University, 2019)
A heavy metal contamination problem in Thailand is an important issue that needs to be addressed urgently, particularly contaminated in water. Heavy metal contamination in water can spread to other environments faster. This research aims to apply chitosan-magnetic biochar synthesized from water hyacinth in order to solve the problem of copper and nickel contaminated in water. Data from SEM indicated that chitosan-magnetic biochar had a smoother surface and had smaller holes than the magnetic biochar. When tested with Autosorb-1, results indicated that the adsorbent with chitosan had a slightly lower porosity compared to without chitosan. Data from FTIR found evidence of chitosan on the adsorbent. According to the XRD study, peaks of iron oxide presented. The point of zero charges (pHPZC) of chitosan-magnetic biochar was 7.03. The adsorption isotherms, kinetics, and thermodynamics were observed. The adsorption of both Cu and Ni followed Langmuir isotherm. The value of qmax for Cu was 38.4615 mg/g and for Ni was 0.4858 mg/g. The R2 value of Dubinin-Radushkevich isotherm was also high. The E value of Cu and Ni was 0.316 kJ/mol and 1.8962 kJ/mol, respectively. The best-fitting kinetic model for Cu was the pseudo-second-order model and for Ni was the intra-particle diffusion. The adsorption was an endothermic process. The process was spontaneous at high temperatures and non-spontaneous at low temperatures.
Keywords: Adsorption; Chitosan; Magnetic biochar; Metal; Wastewater